MELAS/LS Overlap Syndrome Associated With Mitochondrial DNA Mutations: Clinical, Genetic, and Radiological Studies - Wei, Yanping; Huang, Yan; Yang, Yingmai; Qian, Min (Frontiers in Neurology, 2021)
Introduction: The mitochondrial encephalomyopathies are characterized by considerable clinical and genetic heterogeneities. Mitochondrial encephalomyopathy with lactate acidosis and stroke-like episodes (MELAS) and Leigh syndrome (LS) are both established mitochondrial syndromes, sometimes they can overlap. Methods: An observational cohort study was done to analyze the clinical manifestations, biochemical findings, neuroimaging and genetic data, disease outcomes of 14 patients with identified MELAS/LS overlap syndrome. Results: A total of 14 patients, 9 males and 5 females were enrolled. The median age at onset was 14 years, while the average age was 12.6 years. As for clinical features in concordance with MELAS, the first three commonest symptoms were seizures, cognitive impairment and SLE. Brain atrophy was present in 7 patients. As for the clinical hallmarks of LS, the first three commonest symptoms were ataxia, spastic paraplegia and bulbar palsy. Patients presented with individual syndrome or overlap syndromes with similar frequency, and the prognosis didn’t seem to be related to the initial presentation. 13 patients were identified with MTND mutations, among which m.13513G>A mutation in ND5 gene was the most common. Only one patient was found m.8344A>G mutation of MTTK gene. Discussion: Our study demonstrated MTND genes are important mutation hot spots in MELAS/LS overlap syndrome. The follow-up is very important for the final diagnosis of overlap syndrome.